1988
DOI: 10.1111/j.1469-7610.1988.tb00757.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Effects of Cranial Irradiation in Leukaemia: A Survey and Meta‐analysis

Abstract: Central nervous system (CNS) prophylaxis involving cranial irradiation has frequently been found to result in cognitive deficits in survivors of childhood acute lymphoblastic leukaemia. The existence of this effect is still controversial, however, as is the question of factors that might affect its severity. The literature is surveyed and a meta-analysis undertaken on 30 IQ comparisons, which shows a substantial average decrement in irradiated subjects. The effect is larger when radiation is administered at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
1
6

Year Published

1994
1994
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(85 citation statements)
references
References 45 publications
2
74
1
6
Order By: Relevance
“…A number of variables moderate the effect of CR on intellectual outcomes. Girls [Bleyer et al, 1990;Waber et al, 1990Waber et al, , 1992Iuvone et al, 2002] and children radiated at a younger age show lower IQs [Moss et al, 1981;Jannoun, 1983;Cousens et al, 1988;Bleyer et al, 1990;Kingma et al, 1993;Jankovic et al, 1994]. Longer time since treatment is also associated with lower intellectual scores [Rubenstein et al, 1990;Moore et al, 1991].…”
Section: Cranial Radiationmentioning
confidence: 98%
See 1 more Smart Citation
“…A number of variables moderate the effect of CR on intellectual outcomes. Girls [Bleyer et al, 1990;Waber et al, 1990Waber et al, , 1992Iuvone et al, 2002] and children radiated at a younger age show lower IQs [Moss et al, 1981;Jannoun, 1983;Cousens et al, 1988;Bleyer et al, 1990;Kingma et al, 1993;Jankovic et al, 1994]. Longer time since treatment is also associated with lower intellectual scores [Rubenstein et al, 1990;Moore et al, 1991].…”
Section: Cranial Radiationmentioning
confidence: 98%
“…Difficulties emerged over time [Moss et al, 1981;Twaddle et al, 1983], and were evident as early as 1 year following treatment in younger children [Stehbens et al, 1983]. An early meta-analysis of CR studies [Cousens et al, 1988], the majority of which utilized 2,400 cGy, documented an IQ loss of 9 to 10 points relative to controls and population norms. Beyond IQ, Dowell et al [1991] reported that memory and attention were negatively correlated with radiation dose.…”
Section: Cranial Radiationmentioning
confidence: 99%
“…CNS-directed treatment is a standard component of therapy for ALL. Evidence of a detrimental effect of prophylactic cranial irradiation on neurocognitive function in children with ALL (Cousens et al, 1988;Jankovic et al, 1994;Meadows et al, 1981) has resulted in reduction of the use of cranial irradiation and the development of chemotherapy-only protocols with the same or better rate of treatment success (Kamps et al, 2002;Tubergen et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Irradiation-induced cognitive dysfunction may be due to damage to the hypothalamus, resulting in personality Irradiation Effects in Children Cousens et al [32], who conducted a meta-analysis on changes and impairment of cognitive capabilities such as reduced attention span, memory loss and reasoning abil-30 studies of childhood leukaemia assessing the effects of central nervous system prophylactic treatment, which ity [41]. Another possibility is that irradiation-induced vascular injury is followed by ischaemia and hypoxia in includes cranial irradiation therapy (CRT), on intelligence, concluded that childhood leukaemia appears to the hippocampal region in particular, which may be responsible for memory impairment [42].…”
Section: Effects Of Treatment For Pituitary Tumoursmentioning
confidence: 99%